Detection of Anti-Patterns in the Control Flow of Collaborative Business Processes - Roa, Jorge (2015)
The verification of the behavior of Collaborative Business Processes is an important aspect to consider when developing inter-organizational systems. In this work, a verification approach for the control flow of collaborative processes based on anti-patterns is proposed to improve the performance of verification. The approach supports the verification of complex constructs for advanced synchronization, multiple instances, and exception management. To this aim, 10 anti-patterns were defined from a repository of process models, and a tool which implements the anti-patterns was developed to evaluate the verification approach. Results indicate that, at worst, the verification time is less than half a millisecond, even for models with complex control flow constructs.